Hubungan Dukungan Sosial Dengan Kualitas Hidup Lansia Di Posyandu Lansia Wiguna Karya Kebonsari Surabaya - Endah Cahya; Hanna Harnida; Vivin Indrianita (2019)
This study aims to look at the relationship between Social Support and Quality of Life in the Elderly. Social support is a physical change that occurs in the elderly, associated with psychosocial changes, the effect that arises due to changes in the elderly if handled properly, tends to affect the health of the elderly as a whole which leads to the quality of life of the elderly. Psychological problems experienced by the elderly at home are part of the component that determines the quality of life of the elderly associated with social support. Family support that is meaningful will have a positive impact on the elderly in fostering their social relationships and maintaining health status at the posyandu lansia wiguna by kebonsari in the city of Surabaya. This study uses analytical design that aims to find variables. The approach used is the cross sectional approach. The study population was elderly aged 60-80 years. The sample was chosen by using purposive sampling and obtained a sample of 28 elderly people. Data collection using a questionnaire and Chi Square test. Research results Social support from 28 respondents social support was less 17 (60.7%), enough support 1 (3.6%), and good support 10 (35.7%). The quality of life of the 28 respondents, 17 (60.7%) quality of life, high quality of life 1 (3.6%), and very good quality of life (35.7%). Chi Square Test Results (p = 0.001) showed a relationship between social support and the quality of life of the elderly with p = 0.001 smaller = 0.05. In connection with this matter, it is expected that nurses specifically provide information about the importance of social support for the quality of life of the elderly